2016
DOI: 10.1038/srep30783
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive low-frequency electromagnetic stimulation of the left stellate ganglion reduces myocardial infarction-induced ventricular arrhythmia

Abstract: Noninvasive magnetic stimulation has been widely used in autonomic disorders in the past few decades, but few studies has been done in cardiac diseases. Recently, studies showed that low-frequency electromagnetic field (LF-EMF) might suppress atrial fibrillation by mediating the cardiac autonomic nervous system. In the present study, the effect of LF-EMF stimulation of left stellate ganglion (LSG) on LSG neural activity and ventricular arrhythmia has been studied in an acute myocardium infarction canine model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…A canine study found reduced incidence of ischemic-induced VAs when low-frequency EMF was applied to the LSG area at 1 Hz, with 8 s "on", 10 s "off" and intensity at about 90% of motor threshold. 89 A similar result was observed using optogenetic techniques, which combines optical stimulation and genetic modification of target cells, to suppress genetically modified LSG neuronal activity in canines. 90 In the clinic setting, bilateral CSD has been successful in prevention of HF-associated VT or VF storm and may have more prolonged and durable effect on VA suppression when compared to a left sided only procedure alone.…”
Section: Blockade Of Sympathetic Neurotransmissionsupporting
confidence: 60%
See 1 more Smart Citation
“…A canine study found reduced incidence of ischemic-induced VAs when low-frequency EMF was applied to the LSG area at 1 Hz, with 8 s "on", 10 s "off" and intensity at about 90% of motor threshold. 89 A similar result was observed using optogenetic techniques, which combines optical stimulation and genetic modification of target cells, to suppress genetically modified LSG neuronal activity in canines. 90 In the clinic setting, bilateral CSD has been successful in prevention of HF-associated VT or VF storm and may have more prolonged and durable effect on VA suppression when compared to a left sided only procedure alone.…”
Section: Blockade Of Sympathetic Neurotransmissionsupporting
confidence: 60%
“…Techniques for modulation at this level of the ANS with electromagnetic fields (EMFs) and optogenetics have also been tried but remain experimental. A canine study found reduced incidence of ischemic‐induced VAs when low‐frequency EMF was applied to the LSG area at 1 Hz, with 8 s “on”, 10 s “off” and intensity at about 90% of motor threshold . A similar result was observed using optogenetic techniques, which combines optical stimulation and genetic modification of target cells, to suppress genetically modified LSG neuronal activity in canines .…”
Section: Effects Of Neuromodulation On Ventricular Arrhythmiasmentioning
confidence: 65%
“…Acute ischemia was established by left anterior descending occlusion (LADO) for 60 minutes and confirmed by changes in the acute ST segment and T wave on surface ECG. The VA during the 60 minutes after myocardial ischemia, including ventricular tachycardia (VT, ≥3 consecutive premature ventricular beats) and ventricular fibrillation (VF), was recorded by the Lead 7000 system and numbered manually after the experiment according to Wang et al [16].…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of LSG function and neural activity uses the method of Wang et al [16] and Huang et al [17], and the methods' description partly reproduces their wording. Briefly, high-frequency stimulation (HFS; 20 Hz, 0.1 ms pulse duration at different voltages) was applied to LSG using a Grass-S88 stimulator (Astro-Med, West Warwick, Rhode Island, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Different parameters (frequencies and amplitudes) of stimulation contribute to different results. Recently, Wang et al (2016) showed that EMF stimulation located on the surface of the left stellate ganglion could effectively reduce sympathetic activity and the incidence of ventricular arrhythmias in myocardial infarction canine models. EMF stimulation was applied with low frequency (1 Hz, intensity at ∼90% of the motor threshold; 8 s on, 10 s off).…”
Section: Electromagnetic Fields In the Cans And Cardiovascular Diseasesmentioning
confidence: 99%